Health care access for rural youth on equal terms? A mixed methods study protocol in northern Sweden - Isabel Goicolea; Dean Carson; Miguel San Sebastian; Monica Christianson; Maria Wiklund; Anna-Karin Hurtig (BMC, 2018)
Abstract Background The purpose of this paper is to propose a protocol for researching the impact of rural youth health service strategies on health care access. There has been no published comprehensive assessment of the effectiveness of youth health strategies in rural areas, and there is no clearly articulated model of how such assessments might be conducted. The protocol described here aims to gather information to; i) Assess rural youth access to health care according to their needs, ii) Identify and understand the strategies developed in rural areas to promote youth access to health care, and iii) Propose actions for further improvement. The protocol is described with particular reference to research being undertaken in the four northernmost counties of Sweden, which contain a widely dispersed and diverse youth population. Methods The protocol proposes qualitative and quantitative methodologies sequentially in four phases. First, to map youth access to health care according to their health care needs, including assessing horizontal equity (equal use of health care for equivalent health needs,) and vertical equity (people with greater health needs should receive more health care than those with lesser needs). Second, a multiple case study design investigates strategies developed across the region (youth clinics, internet applications, public health programs) to improve youth access to health care. Third, qualitative comparative analysis of the 24 rural municipalities in the region identifies the best combination of conditions leading to high youth access to health care. Fourth, a concept mapping study involving rural stakeholders, care providers and youth provides recommended actions to improve rural youth access to health care. Discussion The implementation of this research protocol will contribute to 1) generating knowledge that could contribute to strengthening rural youth access to health care, as well as to 2) advancing the application of mixed methods to explore access to health care.